Cognitive Processes in Solving the Ill-Structured Problems of Management Sciences of Malaysian Undergraduate Business Degree Students - Cheng, Sheila (2015)
Problem solving is regarded by many educators as the most meaningful and important way of learning and thinking. The ability to aptly apply cognitive skills in problem solving is considered as the fundamental and crucial aspect in a human life. Problems are generally classified and represented by a continuum from well-structured to ill-structured (IS). Both well- and ill-structured problems are different in nature. Well-structured problems are often used in classroom while the ill-structured problems are normally confronted in the real world. Many studies have indicated that Malaysian graduates do not possess the required problem solving skills to meet the societal and industrial demands, especially with the increase in complexity of problems in this millennium. This study explored the cognitive processes and pathways used by Malaysian undergraduate business degree students (UBD) in solving ill-structured (IS) MS problems. The crux of Management Science (MS) is to equip students in problem solving skills during their formal education. A sample 42 UBD students from six tertiary institutions were selected for this case study. Obtrusive observations and in-depth interviews were conducted as techniques for data collection. The cognitive processes were determined from behaviour and performance exhibited by participants while they were delineating the concepts, propositions and strategies in their solution paths. The problem solving sessions using the „think aloud‟ approach were audio- and video-recorded. All written responses and transcripts of video-recordings and interviews in the problem solving sessions were transcribed, analysed, triangulated and classified into episodes of strategies for the interpretations of the cognitive processes. The findings from this study reveal that non-linear pattern of cognitive processes was evident. The pathway to solving the problem had influenced the individual‟s decision-making outcomes. However, there were similarities and differences in cognitive processes between successful and unsuccessful solvers. The study suggests significant implications for the development of effective MS pedagogies and improvements in the design of instructional materials. It is anticipated that problem solving skills of UBD could be enhanced through the learning ability in solving the MS ill-structured problem during their formal education, henceforth, meeting the challenges of societal and industrial demands and expectations.